PENGEMBANGAN BAHAN AJAR KOMIK BERBASIS PENDIDIKAN KARAKTER UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH PADA MATERI SEGIEMPAT - Saputro, Bagus Ardi; Sari, Diana Puspita (JURNAL e-DuMath, 2016)
The research aims to enhance the problem solving on a rectangular material and to produce a decent learning tools used in learning. This study uses the ADDIE model development phase Analysis, Design, Development, Implementation, Evaluation. The population in this research is class VII SMP N 29 Semarang. The results of the validation expert and student questionnaire mostly indicate the criteria very well. So the device is valid to implement. The results showed teaching materials based comic character education to enhance the problem-solving rectangular material is worthy of (valid) or can be used as teaching materials. Problem solving ability of students to use teaching materials are also comics more effective than student learning outcomes using conventional learning model in the subject matter quadrilateral.